Record of tritrophic relationship between Syagrus coronata (Martius) Beccari (Arecaceae), Pachymerus nucleorum Fabricius (Coleoptera: Chrysomelidae: Bruchinae) and Heterospilus sp. (Hymenoptera: Braconidae) in the State of Alagoas, northeastern Brazil - Duarte de Melo, Jefferson; Cajé, Suianne Oliveira dos Santos; Lima, Iracilda Maria de Moura (EntomoBrasilis, 2021)
Some conservation units in Brazil border urban areas, like the Catolé and Fernão Velho Environmental Protection Area (EPA) in the State of Alagoas. In urban areas, there is the habit of cultivating plants for landscape purposes, and Syagrus coronata (Martius) Beccari (Arecaceae), “Licuri” or “Ouricuri”, is a palm tree commonly used in ornamentation; a native species from Caatinga and Atlantic Forest biomes widely explored through time. Some insects have part of their development associated with plants, and Pachymerus nucleorum Fabricius (Coleoptera: Chrysomelidae: Bruchinae) has a close connection with some Arecaceae. Females usually lay eggs on the surface of fallen fruits and the immatures feed on the seed under the drupe endocarp; the larvae, even protected by the hard surface could be preyed by skilled parasitoid wasps. Here, the record of a tritrophic relationship between S. coronata, P. nucleorum, and a wasp of the genus Heterospilus (Hymenoptera: Braconidae) in an urbanized region of Alagoas, close to a remnant of Atlantic Forest of the Catolé and Fernão Velho EPA is communicated. Fruits were collected from the soil surface under the canopy of Licuri palms in the “Universidade Federal de Alagoas” A. C. Simões Campus and transported for laboratory monitoring. Either adults of Heterospilus parasitoid wasps and P. nucleorum beetles from some fruits were recorded. The specimens of S. coronata had seeds preyed upon by P. nucleorum close to a remnant of the Atlantic Forest. The record of a tritrophic relationship involving Heterospilus seems to indicate the tenacity of natural biological control.